2009
DOI: 10.1111/j.1553-2712.2009.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Rapid HIV Screening in a Southeastern Emergency Department

Abstract: Objectives: The objective was to assess the acceptance of an emergency department (ED) human immunodeficiency virus (HIV) screening program based on the Centers for Disease Control and Prevention (CDC) recommendations for routine HIV screening in health care settings.Methods: Rapid HIV screening was offered on an opt-out basis to patients aged 13 to 64 years presenting to the ED by trained HIV counselors. Patients were excluded if they had a history of HIV, were physically or mentally incapacitated, did not un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 35 publications
(77 reference statements)
4
33
2
Order By: Relevance
“…Opt-out testing resulted in higher test acceptance rates in one study (91%) (Freeman et al, 2009) but not another (53%) (Brown et al, 2007) than the routine testing studies that used an opt-in approach in this analysis for which about 50% of persons accept testing (CDC, 2007;Lyss et al, 2007, Silva et al, 2007, White et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opt-out testing resulted in higher test acceptance rates in one study (91%) (Freeman et al, 2009) but not another (53%) (Brown et al, 2007) than the routine testing studies that used an opt-in approach in this analysis for which about 50% of persons accept testing (CDC, 2007;Lyss et al, 2007, Silva et al, 2007, White et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In the existing staff model, triage nursing staff demonstrated the ability to offer HIV screening to a large number of eligible patients. Many patients who were offered and agreed to testing, however, were not tested, likely because of the ED staff's competing clinical responsibilities (Freeman, Sattin, Miller, Dias, Wilde, 2009;White et al, 2009). The supplemental staff model was able to offer testing to fewer patients but tested a higher proportion of patients who accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Freeman et al reported that 91% of patients offered testing in an ED accepted, and they also found that white and married patients were less likely to accept testing. 19 Another study of ED patients by Haukoos et al reported a patient acceptance rate of 81%, regardless of whether testing was opt-out or opt-in. 20 Brown and coworkers reported that 59.7% of ED patients accepted testing.…”
Section: Discussionmentioning
confidence: 99%
“…6 ED-based screening programs are feasible and well received by patients. [7][8][9][10][11] However, the majority of studies have been conducted outside of the Deep South. This article is a descriptive report of an ED-based rapid HIV screening program in the Deep South using the 2006 CDC recommendations.…”
Section: Introductionmentioning
confidence: 99%